ROLE OF ELECTRIC RICKSHAWS IN LANKA TOWN AND ITS HINDER LANES OF HOJAI DISTRICT, ASSAM - Siya Ram Chouhan (EPRA International Journal of Research and Development (IJRD), 2023)
Electric rickshaws are three wheeler battery operated para transit vehicles. From economic point of view they are far better than auto rickshaws which are run on petrol or diesel. India, Govt. had been funding with the help of Ministry of Non-conventional energy sources(MNES) to design and develop more safe and economic variety of E-rickshaws since 2000 till date. The present study on E- rickshaw is made to know role of E- rickshaws in passenger movement in Lanka town and its hinder lanes. Drivers of para transit was interviewed to know their socio-economic status and how it provide employment to poor literate in habitant of Lanka to serve their family livelihood. It is a cheap and environment friendly means of transport in town areas which produces negligible air pollution. Hence, conventional (petrol/diesel) auto-rickshaws are going to become past and E-rickshaws are going to become future day by day.